Impact of different surgical and postoperative adjuvant treatment modalities on survival of sinonasal malignant melanoma - Meng, Xin-Jun (BioMed Central, 2014)
BACKGROUND: The role of postoperative adjuvant treatment for sinonasal malignant melanoma remains unclear. This study evaluates the impact of three different surgical and postoperative adjuvant treatment modalities: surgery alone(open and endoscopic approaches), surgery plus radiotherapy and surgery, radiotherapy plus chemotherapy on survival of patients with primary sinonasal malignant melanoma (SMM). METHODS: The data of 69 patients who underwent primary surgical treatments at Eye & ENT hospital of Fudan University between January 1st, 2000 and December 31st, 2010 were retrospectively reviewed. Survival comparison of different surgical and postoperative adjuvant treatment modalities (surgery alone, surgery plus radiotherapy and surgery, radiotherapy plus chemotherapy), as well as survival comparison between open and endoscopic surgical approaches were performed. Curves depicting survival were performed using Kaplan-Meier method. Statistical analysis was performed using log-rank test software SPSS19 and p < .05 is considered as statistically significant. RESULTS: The median overall survival time was found to be 18 months for surgery alone (27 cases), 32 months for surgery plus radiotherapy (24 cases), 42 months for surgery, radiotherapy plus chemotherapy (18 cases). The 3 and 5 year survival rates for groups mentioned above were 14.8% and 5.6%, 45.1% and 31.6%, 55% and 32.1%, respectively. Statistical significances were found not only between surgery alone and surgery plus radiotherapy treatment group (P = 0.012), but also surgery alone and surgery, radiotherapy plus chemotherapy group (P = 0.002). There was no statistically significant survival difference found between the two different surgical approaches (41 cases for open approach and 28 cases for endoscopic approach). CONCLUSIONS: Sinonasal malignant melanoma is a disease with a poor prognosis. Patients who underwent surgery plus radiotherapy or surgery, radiotherapy plus chemotherapy had better survival outcomes than those underwent surgery alone. Endoscopic approach provided similar survival outcome as an open approach.